On the relationship between adaptation and mitigation - Ralph Winkler (University of Bern, Department of Economics, 2023)
Many poor countries are ill-adapted to the current leave alone a changing future climate, because they lack the necessary financial means to invest in efficient and costeffective safeguarding measures. International endeavours to fund institutions, such as the Green Climate Fund, to provide financial assistance in this respect have not been as successful has hoped for. In this paper, I set up a simple two-player two-stage model, in which a rich country (North) can invest into adaptation measures in a poor country (South). I show that a necessary condition for North to invest into adaptation investments in South is that this results in decreasing equilibrium emissions of South. I find that this can only happen if the funded adaptation measures also have a flavor of mitigation, i.e., apart from safeguarding South from climate damages they have to reduce South's marginal abatement costs. My results have important policy implications for the selection of adaptation and mitigation projects by international adaptation funding organizations, such as the Green Climate Fund.
Keywords: C72; D62; H41; Q54; Q58; 330; Climate change; adaptation versus mitigation; cross-country adaptation investments; non-cooperative climate policy; strategic complementarity